Factors Influencing Community Visits At Integrated Coaching Posts - Dini Afriani; Gita Arisara; Jihan Kanila Pratami; Taufik Suhendar (LP3M Universitas Muhammadiyah Tasikmalaya, 2024)
Situ Health Center is a health center that has six Non-Communicable Disease Integrated Coaching Posts covering five villages and one sub-district. Based on the results of the preliminary study, interviews with the Integrated Coaching Post program holder and ten target communities of the Integrated Coaching Post showed several obstacles in the implementation of the Integrated Coaching Post, including the lack of facilities or equipment, irregular attendance of participants every month and inadequate coverage exceeding the target. Based on this background, researchers are interested in conducting research on the Integrated Coaching Post. This study aims to describe the factors that influence community visits to the Integrated Development post at the Situ Health Center, North Sumedang District, Sumedang Regency in 2023. This study uses a quantitative form with a cross sectional approach. The population in this study were all people in the Situ Health Center area aged 15-59 years, totaling 31,778 people. The sampling technique used Accidental Random Sampling technique so that a sample of 100 people was obtained. The results showed that there was a relationship between Cadre Support (p=0.000), Family Support (p=0.000) and there was no relationship between Education (p=0.838) with Community Visits at the Integrated Development Post. The results and suggestions of this study are expected to be input for the Situ Health Center in improving the service of Integrated Development post activities. It is also expected to provide experience and insight in developing research at the Health Center, especially regarding the activities of the Integrated Development post.